Development of a Rapid and Accurate Nanopore-based Sequencing Platform for on-Field Identification of Beer-Spoilage Bacteria in the Breweries. (1st July 2021) - Kurniawan, Yohanes Novi; Shinohara, Yuji; Takesue, Nobuchika; Sakai, Hiroaki; Magarifuchi, Tetsuro; Suzuki, Koji
Abstract: When a beer is contaminated with unknown microorganisms, rapid and accurate identification of the contaminants and risk assessment of their spoilage capability are of critical importance for proper corrective actions. Molecular-based identification techniques have been used for years to identify beer-spoilage bacteria in the breweries. However, these techniques require expensive, advanced analytical instruments (e.g., DNA sequencer, MALDI-TOF MS, etc.), and advanced skills, hindering their practical use for routine microbiological testing in the field. Thus, the evaluation and development of alternative methods for microbial identification that are low-cost, but rapid and provide the same level of accuracy, are a necessity. One particular technology is the nanopore-based sequencer, MinION, developed by Oxford Nanopore Technologies (ONT). MinION is a low cost, portable real-time device for DNA and RNA sequencing. We developed and evaluated a MinION sequencer-based platform for beer-spoilage bacterial identification. The near full length 16S rRNA gene of a wide variety of beer-spoilage bacteria and those commonly found in the brewery environment, were sequenced using three different sequencing kits and analyzed using the EPI2ME cloud-based analysis platform and a consensus sequence-based approach. The methods successfully rapidly identified test-microorganisms at a species level, (approx. 3.5 h from DNA extraction to data analysis) and with a high accuracy, similar to Sanger sequencing (average per. identity > 98.5%). The MinION sequencer-based microbial identification platform was shown to be a powerful tool for on-field rapid and accurate beer-spoilage bacterial identification, which could revolutionize the way microbial identification is performed in a brewery QC laboratory.